Epistemes del presente y saberes locales. Provocaciones y alternativas: cognición y metacognición - Mallarino Flórez, Claudia (Universidad de San Buenaventura - Cali, 2017)
The information in this article is taken subjectively, i.e. it is embodied in a complex of values, beliefs, languages, desires, previous knowledge, dreams, and memories taken from daily life to acquire knowledge as a result of its development, seizure, appropriation, implementation, transfer, and critical and relevant use of it. This movement however, is only a piece of the smart process of knowing, which is not enough without visualizing the mental dynamics that makes possible such an experience. When we discover what we know and how this happens, not only from the particularity of the disciplines (methodology/epistemology) but from the peculiarity of the mind (epistemology/episteme), we will have the alternatives and strategies to produce knowledge and we will be freed from the systematic habit of reproducing information. Those questions on the nature of human knowledge and the evolution of ideas about how knowledge is possible, on the nature of human development, on how heredity and the environment contribute to it, and on the nature of the world and its operation, are understood as: what are my routes of knowledge?, how I can use these cognitive routes in other contexts? and how can I set patterns/habits to get to know different contents in multiple contexts? i.e., how to design higher-order cognitive strategies that can be transferred and generalized?